Triada przewagi konkurencyjnej w obliczu niepewności - Stańczyk, Sylwia (The fundamental factors of competitiveness' superiority in the face of uncertainty, 2006)
The purpose of this paper is to present important elements of future organizations in current conditions of progressive globalization and tendency to create homogenious market. Moreover, this paper is an attempt to specify organizational elements needed as a fundamental factor of succes. The considerated problems and conclusions are mainly based on literature studies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 265-273